2015
DOI: 10.3109/0886022x.2015.1033634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance exercise training on acyl-ghrelin and obestatin levels in hemodialysis patients

Abstract: Background: Patients undergoing hemodialysis (HD) present altered levels of appetite hormones such as acyl-ghrelin (orexigenic) and obestatin (anorexigenic), which may contribute to anorexia. Physical exercise may affect these hormones and improve appetite in these patients. Objectives: The objective of this study is to evaluate the effects of a resistance exercise program in appetite hormones, body composition, and nutritional status in HD patients. Design: Intervention study with the control group. Subjects:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
(36 reference statements)
1
17
0
7
Order By: Relevance
“…Our study also showed that high‐sensitivity C‐reactive protein (hs‐CRP), as a marker of chronic inflammation in dialysis patients, did not undergo significant changes after 12 weeks of physical exercise. The selection of hs‐CRP as a marker of inflammation in our study was due to its strong correlation with cardiovascular prognostic factors . In addition, hs‐CRP has a long half‐life and is independent of other factors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also showed that high‐sensitivity C‐reactive protein (hs‐CRP), as a marker of chronic inflammation in dialysis patients, did not undergo significant changes after 12 weeks of physical exercise. The selection of hs‐CRP as a marker of inflammation in our study was due to its strong correlation with cardiovascular prognostic factors . In addition, hs‐CRP has a long half‐life and is independent of other factors .…”
Section: Discussionmentioning
confidence: 99%
“…The selection of hs-CRP as a marker of inflammation in our study was due to its strong correlation with cardiovascular prognostic factors. 28 In addition, hs-CRP has a long half-life and is independent of other factors. 29 However, our study showed that the hs-CRP level of the subjects had a wide range of variation, which may hinder the analysis between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Obestatin decreased and acyl-ghrelin increased significantly among patients of the exercise group. 8 A study with obese/overweight women showed no effect of moderate intensity acute exercise (running at 50% of VO2 max ) on obestatin levels. 30 A single circuit-resistance exercise had no effect on plasma obestatin levels in female college students; however, the authors reported that GH levels increased significantly and concluded that obestatin, likewise acyl-ghrelin, does not contribute to circuit-resistance exercise-induced increase in GH.…”
Section: Discussionmentioning
confidence: 99%
“…A study of our group showed that 6 months of resistance exercise in hemodialysis (HD) patients was effective in reducing obestatin and increasing acyl-ghrelin levels. 8 However, the effects of acute exercise on appetite hormones levels were not evaluated in CKD patients. Then, the objective of this study was evaluating the effects of a single bout of resistance exercise on acyl-ghrelin and obestatin plasma levels of CKD patients undergoing HD.…”
Section: Introductionmentioning
confidence: 99%
“…Moraes et al [58] reported that acyl-ghrelin increased after a six month of resistance exercises in hemodialyresistance exercises in hemodialysis patients. Martins et al [50] reported that body weight decreased while acyl ghrelin and appetite increased after 12-week exercise (75% of HR, 3days/week) program in 22 sedentary and obese women.…”
Section: Ghrelin Response To Chronic Exercise and Appetite And Food Imentioning
confidence: 99%